2020
DOI: 10.3389/fped.2019.00532
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Preoperative Assessment, Classification of Stenosis, Decision-Making

Abstract: Pediatric Laryngo-Tracheal Stenosis (LTS) comprises different conditions that require precise preoperative assessment and classification. According to the guidelines, the optimal diagnostic work-up of LTS patients relies both on a comprehensive anamnesis and on endoscopic and radiological assessments. All the causes of LTS result in an impairment in airflow, mucociliary clearance, phonation, and sometimes in swallowing disorders. The main goals of treatment are to maintain an adequate respiratory space and res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…The ultimate objective of treating tracheal stenosis is to ensure luminal restoration, while preserving phonation and lower respiratory passage protection against aspiration. 14 To achieve these goals, many patients have to undergo more than one treatment modalities. The myriad of treatment modalities range from LASER ablation, possibly combined with dilatation and intraluminal placement of stent.…”
Section: Discussionmentioning
confidence: 99%
“…The ultimate objective of treating tracheal stenosis is to ensure luminal restoration, while preserving phonation and lower respiratory passage protection against aspiration. 14 To achieve these goals, many patients have to undergo more than one treatment modalities. The myriad of treatment modalities range from LASER ablation, possibly combined with dilatation and intraluminal placement of stent.…”
Section: Discussionmentioning
confidence: 99%
“…LTR and CTR correct the stenosis by achieving decannulation, which is tracheostomy tube removal [5]. Studies have shown that 96% of children with subglottic stenosis achieve decannulation when undergoing a posterior graft LTR, which proves to be a very successful treatment and management of subglottic stenosis [9].…”
Section: Discussionmentioning
confidence: 99%
“…8 Includes postponing the case or postponing the intubation and returning with appropriate resources. 9 Other options include, but are not limited to, proceeding with the procedure utilizing a face mask or supraglottic airway ventilation. Pursuit of these options usually implies that ventilation will not be problematic.…”
Section: Discussionmentioning
confidence: 99%
“…The proximity of the scar tissue to the vocal fold is determined and an involvement of the vocal chords or the arytenoid cartilages by the scar tissue is documented. The length of the stenosis and the entire trachea is also measured ( 4 ).…”
Section: Assessmentmentioning
confidence: 99%
“…Figure4 Subglottic stenosis with significant lateral submucosal scar formations is shown in (A). A lateral cricoplasty using a scalpel is performed (B).…”
mentioning
confidence: 99%